RAMADAN FASTING AMONG TYPE 1 DIABETES MELLITUS PATIENTS IN A SINGLE TERTIARY CENTRE - NH, Hamdi; YS, Ng; CV, Tong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Ramadan fasting among patients with Type 1 diabetes mellitus (T1DM) carries a higher risk given the nature of the disease and therapy used. Currently, Ramadan fasting practice among Muslim T1DM patients in our centre is not known. METHODOLOGY This is a questionnaire-based study done among Muslim patients attending the T1DM clinic in Hospital Putrajaya. All Muslim patients attending the clinic from January to April 2024 (before Eid) were given the questionnaire to fill out. RESULTS There were 56 respondents, 22 male and 34 female. The mean age was 30.2 years (± 8.04). The mean duration of illness was 13 years (± 8.39). The majority (79%) of the respondents received tertiary education. Most respondents (88%) have received advice from healthcare providers on Ramadan fasting. Four out of 5 intended to fast during Ramadan. Out of those who intended to fast, 3 quarters had high risk based on the DAR-IDR (Diabetes and RamadanInternational Diabetes Federation) risk calculator. Among all the respondents, 80% had high risk, 18.2% had moderate risk and only 1.8% had low risk. In comparison to the actual risk, only about one-third of total respondents perceived themselves as having high risk, half perceived themselves as moderate risk and the rest felt they had low risk. Forty percent of the respondents correctly estimated their risk of fasting. In terms of diabetes disease knowledge, our respondents had a mean score of 11.7 (± 2.29). Twothirds of the respondents achieved high scores, 30.4% had average scores and only 3.6% had low scores. CONCLUSION Among Muslim T1DM patients in our centre, the majority received tertiary education and had been advised on Ramadan fasting in the past. Despite having high risk, most opted to fast. Therefore, Ramadan fasting education must emphasize measures to fast safely.